Control of Yaws in the Asuogyaman District. Can Community Involvement Make The Difference? - Forgor, A.A. (University of Ghana, 2001)
Community involvement in the control of yaws is a participatory approach to healthcare that is organized from the perspective of the recipient. This study was prompted by the fact that, in 1998 Addofound that community participation in the control of yaws was poor, 3.4% of the population is infected with yaws, yaws now ranking 3rd (1997-2000) from 6th position in 1996. This study looked at how a rural district (Asuogyaman) in the Eastern region of Ghana perceive and manage yaws and the extent to which the communities are involved in the control of the disease. It also looked at the health service and community factors, which affect community participation in the district. Focus group discussions, in-depth interviews, observations (participatory and nonparticipatory) involving 172 participants/respondents (key informants, level B health workers, herbalists and victims of yaws). Yaws was mainly perceived by the community (121 out of 153) to be caused by poor personal and environmental hygiene and sanitation. The disease was perceived by the community (74 out of 95 respondents) to be transmitted mainly by the sharing of toiletries, clothing and direct contact. The prevention of yaws was found to be by health education, avoidance of direct contact with the lesions of the affected person and observation of personal and environmental hygiene and sanitation. Though these perceptions about yaws are true, this knowledge was not reflected in their practices or treatment of the disease. The two main forms of treatment were traditional and modem. "Blue-stone" (copper sulphate) was found to be the most popular form of traditional treatment of the disease by some communities. Of the 153 respondents, 90 did not know that treatment of the disease was available/possible at the hospitals/clinics; 63 knew, 11 had no idea and 48 gave various answers. Health education on yaws was found to be inadequate. Yaws was perceived to have been eradicated and accorded least importance. The participation of the communities in the control of yaws was assessed by using Rifkin's method based on 5 factors- needs assessment, management, resource mobilization, leadership and organization. The participation of the communities was small. Presence of community health structures and their orientation, incentives to community health agents, free treatment, prompt response (by health workers) to reports made by community health agents and frequent interaction between health workers and the communities promoted participation. Knowledge about the disease enhanced participation. Conflicts, embezzlement of funds, failure to act on /respond to complaints made by community health agents, failure to complement community initiatives inhibited community participation. The response rate of the study was 91.5% (172 out of 188). Lack of time, funds and personnel, poor road network, conflicts, rains, limited the study. The Rifkin method itself had limitations. Health education and house-to-house treatment of yaws should be intensified. The study concluded that yaws, which is endemic in the district, could be effectively controlled with community involvement.